A comparison of viral strategies and model systems to target norepinephrine neurons in the locus coeruleus reveals high variability in transgene expression patterns: methods and resources - Wissing, Chantal; Eschholz, Lena; Maheu, Maxime; Sauter, Kathrin; Morellini, Fabio; Wiegert, Simon; Dieter, Alexander (PLoS biology, 2025)
The locus coeruleus (LC) norepinephrine (NE) system is involved in a variety of physiological and pathophysiological processes. Refining our understanding of LC function largely relies on selective transgene expression in LC-NE neurons, allowing targeted manipulation and readout of noradrenergic neurons. Here, we performed a side-by-side comparison of the most commonly used strategies to genetically target the LC, including different cre driver lines and promoter-mediated transgene expression. We report differences between these strategies in terms of transgene expression efficacy and specificity. Parallelly, we found no behavioral alterations in cre-expressing mice of any mouse line compared to wild-type littermates. Finally, to further facilitate the investigation of LC-NE function, we created a suite of constructs, including a reporter protein, a calcium indicator, and a light-driven cation channel, whose expression is mediated by the previously described PRS×8 promoter. These constructs allow identification, monitoring, and manipulation of LC-NE activity either in wild-type mice, or in combination with tissue-specific manipulations of different cre driver lines. The results of our study are crucial for the interpretation of previous experiments using the respective targeting strategies, as well as for the design of future studies.